Terror.edu: Terror and Education in the U.S.A. (American Journal of Islam and Society, 2010)
The Society for Critical Exchange held its first Winter Theory Institute from11-14 February 2010 at the University of Houston-Victoria, located inVictoria, Texas. Eleven scholars from a variety of disciplines and fromacross the United States came together to present and discuss their currentwork on questions regarding the affect terror and terrorism are having oneducation in higher education. The participants presented their work by turn,and all took part in the intense two days fully devoted to the discussions.Some of the questions we hoped to address included the following: Howhave institutions of higher learning responded to the specter of terror? Howshould academe respond? What is our professional role in a terroristicworld? ...